Graft copolymer, curable resin composition containing same, and method for producing same
Patent Information
- Application Number
- JP2023528740
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-02
- Filing Date
- 2022-03-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-03-02
AI Technical Summary
【0027】 本発明のグラフト共重合体は、エポキシ樹脂などのような硬化性樹脂に対する粉体分散性に優れるため、硬化性樹脂組成物に粉体状分散方法により分散が可能であるという効果がある。
Smart Images

Figure 0007642068000007 
Figure 0007642068000008 
Figure 0007642068000001
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of priority based on Korean Patent Application No. 10-2021-0028992 filed on March 4, 2021, and all contents disclosed in the documents of the Korean patent application are incorporated as part of this specification.
[0002] The present invention relates to a graft copolymer which has excellent powder dispersibility in curable resins such as epoxy resins and can be used as a powdery impact modifier, a curable resin composition containing the same, and a method for producing the same. [Background technology]
[0003] Curable resins, such as epoxy resins, are used in various fields, such as electrical and electronic products, automobile parts, and building materials. The curable resins are used in combination with additives, such as inorganic fillers, release agents, and rubber particles having rubber properties, for the purpose of improving physical properties and processability, rather than being used alone. Among them, epoxy resins often exhibit brittle properties, and therefore need to be improved in terms of impact resistance and adhesive strength.
[0004] As a method for improving the impact resistance of epoxy resins, a method has been proposed in which a graft copolymer containing a rubber polymer is used as an impact modifier. The graft copolymer has a core-shell structure including a core containing a rubber polymer and a shell formed by graft polymerization onto the core.
[0005] Here, in order to apply the graft copolymer as an impact modifier for epoxy resin, it is necessary to disperse the graft copolymer in the epoxy resin. Methods for dispersing the graft copolymer in the epoxy resin include a liquid dispersion method and a powder dispersion method.
[0006] In the liquid dispersion method, the graft copolymer is dispersed in epoxy resin by a stepwise solvent replacement method in which the graft copolymer in a latex state in which the graft copolymer is dispersed in water is replaced with a solvent and the solvent is replaced again with epoxy resin as shown in Figure 1. This liquid dispersion method has the advantage that the graft copolymer is dispersed in a homogeneous distribution matrix of epoxy resin, but in order to apply the graft copolymer to epoxy resin as an impact modifier, there is a storage problem in that the graft copolymer must be stored in a latex state until it is dispersed, the process cost due to the solvent replacement is high, and there is an environmental problem due to the graft copolymer and the water and solvent that are separated and discharged during the solvent replacement process.
[0007] The powder dispersion method, as shown in FIG. 2, has an advantage that the process cost is low in that the dry powder aggregated from the graft copolymer latex, i.e., the powder-like graft copolymer, is directly dispersed in the epoxy resin. However, there is a problem that the viscosity of the graft copolymer powder becomes very high when the graft copolymer powder is directly introduced into the epoxy resin, making it very difficult or impossible to disperse the graft copolymer.
[0008] Therefore, in order to apply a powder dispersion method to improve both process costs and environmental aspects when applying an impact modifier to a curable resin composition such as an epoxy resin, it is necessary to improve the powder dispersibility of the graft copolymer powder. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP2006-104328 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been devised to solve the above-mentioned problems of the prior art, and an object of the present invention is to provide a graft copolymer that has excellent powder dispersibility in curable resins such as epoxy resins and can be used as a powdery impact modifier, and a method for producing the same.
[0011] Another object of the present invention is to provide a curable resin composition in which the graft copolymer is applied in powder form, and a method for producing the same. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides a graft copolymer, a curable resin composition, and a method for producing the curable resin composition. (1) The present invention provides a core-shell graft copolymer including a core containing a rubber polymer and a shell formed by graft polymerization of a graft monomer onto the rubber polymer, the graft copolymer containing 72% by weight to 83% by weight of the core, the core having an average particle size of 250 nm or more, and the shell having a weight average molecular weight of 40,000 g / mol or less.
[0013] (2) In the present invention, there is provided the graft copolymer described in (1) above, wherein the rubber polymer contains one or more monomer units selected from the group consisting of conjugated diene monomer units and alkyl acrylate monomer units.
[0014] (3) In the present invention, there is provided the graft copolymer according to (1) or (2) above, wherein the rubber polymer is at least one selected from the group consisting of a homopolymer of a conjugated diene monomer, a copolymer of an aromatic vinyl monomer and a conjugated diene monomer, and an acrylic rubber polymer.
[0015] (4) In the present invention, there is provided the graft copolymer according to any one of (1) to (3), wherein the graft monomer comprises at least one selected from the group consisting of alkyl (meth)acrylate monomers and aromatic vinyl monomers.
[0016] (5) In the present invention, there is provided the graft copolymer according to any one of (1) to (4) above, wherein the graft monomer comprises a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, an aromatic vinyl monomer, and a crosslinkable monomer.
[0017] (6) In the present invention, there is provided the graft copolymer according to (5) above, wherein the crosslinkable monomer is polyethylene glycol diacrylate or allyl methacrylate.
[0018] (7) The present invention provides the graft copolymer according to any one of (1) to (6) above, which comprises 75% by weight to 80% by weight of a core and 20% by weight to 25% by weight of a shell.
[0019] (8) The present invention provides the graft copolymer according to any one of (1) to (7) above, wherein the core has an average particle size of 250 nm to 350 nm.
[0020] (9) The present invention provides the graft copolymer according to any one of (1) to (8) above, wherein the shell has a weight average molecular weight of 30,000 g / mol to 40,000 g / mol.
[0021] (10) In the present invention, there is provided the graft copolymer according to any one of (1) to (9) above, wherein the graft copolymer has an average particle size of 250 nm to 500 nm.
[0022] (11) The present invention provides a curable resin composition comprising a continuous phase and a dispersed phase, the continuous phase comprising a curable resin, and the dispersed phase comprising the graft copolymer according to any one of (1) to (10).
[0023] (12) In the present invention, there is provided the curable resin composition according to (11) above, which contains 50% by weight to 99% by weight of a continuous phase and 1% by weight to 50% by weight of a dispersed phase.
[0024] (13) In the present invention, there is provided the curable resin composition according to (11) or (12) above, wherein the curable resin is an epoxy resin.
[0025] (14) The present invention provides a method for producing a curable resin composition, comprising: a step (S10) of producing a graft copolymer latex containing the graft copolymer described in any one of (1) to (10); a step (S20) of producing a graft copolymer powder by agglomerating and drying the graft copolymer latex produced in the step (S10); and a step (S30) of producing a curable resin composition by mixing a curable resin and the graft copolymer powder produced in the step (S20), wherein the step (S30) is performed by dispersion using a stirrer.
[0026] (15) The present invention provides the method for producing a curable resin composition according to (14) above, wherein the viscosity of the curable resin composition produced in the step (S30) is 2,500 Pa.s or less at 25°C. Effect of the Invention
[0027] The graft copolymer of the present invention has excellent powder dispersibility in curable resins such as epoxy resins, and therefore has the effect of being able to be dispersed in a curable resin composition by a powder dispersion method.
[0028] Since the curable resin composition of the present invention can be applied in powder form as an impact modifier, it has the effect of being excellent in productivity and excellent mechanical properties such as impact resistance due to the graft copolymer dispersed in the curable resin composition. [Brief description of the drawings]
[0029] [Figure 1]FIG. 1 is a process diagram illustrating a liquid dispersion method for dispersing a graft copolymer in an epoxy resin. [Diagram 2] FIG. 1 is a process diagram showing a powder dispersion method for dispersing a graft copolymer in an epoxy resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The present invention will now be described in more detail to aid in understanding the invention. The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0031] In the present invention, the term "monomer unit" may refer to a component, structure, or substance itself originating from a monomer, and as a specific example, may refer to a repeating unit formed in a polymer by an input monomer participating in a polymerization reaction during polymerization of the polymer. As used herein, the term "composition" is inclusive of mixtures of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0032] The present invention provides a graft copolymer applicable as an impact modifier in a curable resin composition. The graft copolymer according to the present invention has improved powder dispersibility in a curable resin such as an epoxy resin, and is a core-shell graft copolymer including a core containing a rubber polymer and a shell formed by graft polymerization of a graft monomer onto the rubber polymer, and the graft copolymer may include 72% to 83% by weight of the core, the core having an average particle size of 250 nm or more, and the shell having a weight average molecular weight of 40,000 g / mol or less. This has the effect of allowing dispersion in a curable resin composition by a powder dispersion method.
[0033] According to one embodiment of the present invention, in the core-shell graft copolymer, the core may refer to the rubber polymer component itself that forms the core or core layer of the graft copolymer, and the shell may refer to a polymer component or copolymer component that is graft polymerized to the rubber polymer to form a shell or shell layer in the form of a shell surrounding the core. That is, the core containing the rubber polymer may be the rubber polymer itself, and the shell may refer to a graft layer formed by graft polymerization of a graft monomer to the rubber polymer.
[0034] According to an embodiment of the present invention, the rubbery polymer is a component for imparting impact resistance when the graft copolymer is applied as an impact modifier, and may include one or more monomer units selected from the group consisting of conjugated diene monomer units and alkyl acrylate monomer units. As a specific example, the rubbery polymer may be a conjugated diene rubbery polymer or an acrylic rubbery polymer. As a more specific example, the conjugated diene rubbery polymer may be one or more selected from the group consisting of a homopolymer of a conjugated diene monomer and a copolymer of an aromatic vinyl monomer-conjugated diene monomer, and the acrylic rubbery polymer may be a homopolymer of an alkyl acrylate monomer.
[0035] According to one embodiment of the present invention, the conjugated diene monomer of the rubber polymer may be at least one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, piperylene, 3-butyl-1,3-octadiene, isoprene, and 2-phenyl-1,3-butadiene, and a specific example thereof may be 1,3-butadiene.
[0036] According to one embodiment of the present invention, the aromatic vinyl monomer of the rubber polymer may be at least one selected from the group consisting of styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, and 1-vinyl-5-hexylnaphthalene, and a specific example thereof may be styrene.
[0037] According to an embodiment of the present invention, the alkyl acrylate monomer of the rubber polymer may be an alkyl acrylate monomer having 1 to 12 carbon atoms, and a specific example thereof may be one or more selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, and n-butyl acrylate, and a more specific example thereof may be n-butyl acrylate.
[0038] According to one embodiment of the present invention, the shell is a component for improving compatibility and mechanical properties when the graft copolymer is used as an impact modifier, and may be a graft layer formed by graft polymerizing a graft monomer onto the rubber polymer as described above. As a specific example, the graft monomer graft polymerized onto the rubber polymer to form the shell may include one or more selected from the group consisting of alkyl (meth)acrylate monomers and aromatic vinyl monomers, and more specifically, may include alkyl (meth)acrylate monomers and aromatic vinyl monomers.
[0039] According to one embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be an alkyl (meth)acrylate monomer having 1 to 12 carbon atoms, and specific examples thereof may be one or more selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, and n-butyl acrylate.
[0040] According to one embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be two or more monomers selected from the group consisting of alkyl (meth)acrylate monomers having 1 to 12 carbon atoms, and specific examples thereof may be two or more monomers selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, and n-butyl acrylate.
[0041] According to an embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be a methyl (meth)acrylate monomer; and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms. In this case, the weight average molecular weight of the shell can be further reduced, and thus, when the graft copolymer is dispersed in the curable resin, swelling of the shell can be minimized, thereby preventing an increase in viscosity. In this case, the alkyl (meth)acrylate monomer may include 50 wt% to 99 wt%, 60 wt% to 90 wt%, or 70 wt% to 85 wt% of the methyl (meth)acrylate monomer; and 1 wt% to 50 wt%, 10 wt% to 40 wt%, or 15 wt% to 30 wt% of the alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.
[0042] According to one embodiment of the present invention, the alkyl (meth)acrylate monomer of the graft monomer may be contained in an amount of 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more, based on the total content of the graft monomer, and may be contained in an amount of 100% by weight or less, 99% by weight or less, 98% by weight or less, 97% by weight or less, or 96% by weight or less.
[0043] According to an embodiment of the present invention, the aromatic vinyl monomer of the graft monomer may be at least one selected from the group consisting of styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, and 1-vinyl-5-hexylnaphthalene, and a specific example thereof may be styrene.
[0044] According to one embodiment of the present invention, the aromatic vinyl monomer of the graft monomer may be contained in an amount of 0.1 wt % or more, 0.5 wt % or more, 1 wt % or more, 3 wt % or more, or 5 wt % or more, based on the total content of the graft monomer, and may be contained in an amount of 20 wt % or less, 15 wt % or less, 10 wt % or less, or 5 wt % or less.
[0045] According to an embodiment of the present invention, the graft monomer may further include a crosslinkable monomer in addition to the alkyl (meth)acrylate monomer and the aromatic vinyl monomer, i.e., the graft monomer may include a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, an aromatic vinyl monomer, and a crosslinkable monomer.
[0046] According to one embodiment of the present invention, the crosslinkable monomer is intended to improve the shell-forming ability by crosslinking during the formation of a shell by the graft monomer, and to further improve the compatibility and mechanical properties of the shell. The crosslinkable monomer may be at least one selected from (meth)acrylic crosslinkable monomers such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and vinyl crosslinkable monomers such as divinylbenzene, divinylnaphthalene, and diallyl phthalate. A specific example of the crosslinkable monomer may be polyethylene glycol diacrylate or allyl methacrylate.
[0047] According to one embodiment of the present invention, when the graft monomer further includes a crosslinkable monomer, the crosslinkable monomer of the graft monomer may be included in an amount of 0.01 wt % or more, 0.05 wt % or more, 0.1 wt % or more, or 1 wt % or more, based on the total content of the graft monomer, and may be included in an amount of 10 wt % or less, 5 wt % or less, or 1 wt % or less.
[0048] In order to make the graft copolymer according to the present invention dispersible in a curable resin composition by a powder dispersion method, it is very important to adjust the content of the core in the graft copolymer, the average particle size of the core, and the weight average molecular weight of the shell.
[0049] According to one embodiment of the present invention, the graft copolymer may contain 72% to 83% by weight of the core, and specifically, 75% to 83% by weight or 75% to 80% by weight, and thus the graft copolymer may contain 17% to 28% by weight, 17% to 25% by weight, or 20% to 25% by weight of the shell. When the graft copolymer is dispersed in the curable resin within this range, the compatibility between the curable resin and the graft copolymer is sufficiently ensured, and the swelling of the shell is minimized, thereby preventing an increase in viscosity. On the other hand, if the graft copolymer contains a core content lower than the above range, the shell content in the graft copolymer must be increased accordingly, which causes a problem that the shell, which has a high affinity with the curable resin, swells, causing an increase in viscosity and a decrease in dispersibility. In addition, if the graft copolymer contains a core at a content higher than the above range, the compatibility of the curable resin and the graft copolymer decreases rapidly, and although the increase in viscosity due to the swelling of the shell can be prevented, there is a problem that dispersion is not substantially performed. Meanwhile, the respective contents of the core and shell may be derived from the content ratio of the rubber polymer and the graft monomer added during the preparation of the graft copolymer.
[0050] According to one embodiment of the present invention, the core may have an average particle size of 250 nm or more, and specifically, the average particle size may be 250 nm to 400 nm, or 250 nm to 350 nm. Within this range, the viscosity can be prevented from increasing when dispersing the graft copolymer in the curable resin. If the average particle size of the core is less than 250 nm, the average particle size of the graft copolymer is inevitably small since the average particle size of the graft copolymer is not increased by the shell, and if the average particle size of the core and the average particle size of the graft copolymer are not large enough, aggregation between small particles occurs, which causes a problem of decreased dispersibility due to an increase in viscosity.
[0051] According to an embodiment of the present invention, the shell may have a weight average molecular weight of 40,000 g / mol or less, and specific examples of the weight average molecular weight may be 15,000 g / mol or more, 17,000 g / mol or more, 30,000 g / mol or more, 32,000 g / mol or more, 39,000 g / mol or less, 36,000 g / mol or less, 35,000 g / mol or less, or 33,000 g / mol or less. Within this range, when the graft copolymer is dispersed in the curable resin, the compatibility between the curable resin and the graft copolymer is sufficiently ensured, and swelling of the shell is minimized, thereby preventing an increase in viscosity. On the other hand, if the weight average molecular weight of the shell is higher than the above range, there is a problem that the shell having a high affinity with the curable resin swells, increasing the viscosity and decreasing the dispersibility. The weight average molecular weight of the shell may be adjusted by adjusting the amount of the initiator and the activator added when the graft monomer is graft polymerized in the presence of the rubber polymer.
[0052] In this manner, by adjusting the content of the core in the graft copolymer, the average particle size of the core, and the weight average molecular weight of the shell according to the present invention, it becomes possible to disperse the graft copolymer in a curable resin composition by a powder dispersion method.
[0053] According to one embodiment of the present invention, the average particle size of the graft copolymer may be 250 nm to 500 nm, 250 nm to 450 nm, or 250 nm to 400 nm. Within this range, an increase in viscosity during dispersion of the graft copolymer in the curable resin can be prevented.
[0054] The present invention also provides a method for preparing the graft copolymer, which includes the steps of (S1) preparing a rubber polymer latex including a rubber polymer having an average particle size of 250 nm or more, and (S2) preparing a graft copolymer latex including a core-shell graft copolymer by adding a graft monomer in the presence of 72% by weight to 83% by weight (based on solid content) of the rubber polymer latex, and the shell of the graft copolymer prepared in the (S2) step may have a weight average molecular weight of 40,000 g / mol or less.
[0055] According to one embodiment of the present invention, in the method for preparing the graft copolymer, the type and content of the monomer for performing each step may be the same as the type and content of the monomer for the graft copolymer described above.
[0056] According to one embodiment of the present invention, the step (S1) is a step for preparing a rubber polymer that forms a core or a core layer in a core-shell graft copolymer, and is characterized in that the average particle size of the rubber polymer particles is adjusted to 250 nm or more. The step (S2) is a step for graft polymerizing the rubber polymer to form a shell or a shell layer in the form of a shell surrounding the core, and is characterized in that the weight average molecular weight of the shell is adjusted to 40,000 g / mol or less.
[0057] According to one embodiment of the present invention, the steps (S1) and (S2) may each be performed by emulsion polymerization, and may be performed in the presence of an emulsifier and an initiator, as well as an electrolyte, a molecular weight regulator, an activator, etc., which are added during emulsion polymerization. In this regard, when performing the step (S1), the average particle size of the rubber polymer particles can be adjusted by the amount of emulsifier added, and when performing the step (S2), the weight average molecular weight of the shell can be adjusted by adjusting the amount of initiator and / or activator added, or by continuously adding a graft monomer.
[0058] According to one embodiment of the present invention, the emulsifier may be at least one selected from the group consisting of fatty acid-based emulsifiers and resin acid-based emulsifiers, and in this case, it has the effect of providing excellent latex stability.
[0059] According to one embodiment of the present invention, the amount of emulsifier added in step (S1) may be 0.1 to 3.4 parts by weight, 1.0 to 3.3 parts by weight, 1.5 to 3.2 parts by weight, 2.0 to 3.2 parts by weight, or 2.1 to 3.1 parts by weight, based on 100 parts by weight of the monomer for polymerizing the rubber polymer. Within this range, the average particle size of the rubber polymer particles can be adjusted to 250 nm or more.
[0060] According to one embodiment of the present invention, the amount of emulsifier added in step (S2) may be 0.1 to 1.0 parts by weight, 0.1 to 0.5 parts by weight, or 0.1 to 0.3 parts by weight, based on 100 parts by weight of the total of the rubber polymer and the monomer for polymerizing the graft copolymer. Within this range, there is an effect of excellent latex stability.
[0061] According to an embodiment of the present invention, the step (S1) may be performed using a water-soluble initiator that can be used in emulsion polymerization, and the water-soluble initiator may be potassium persulfate, sodium persulfate, ammonium persulfate, etc. The step (S2) may be performed by radical polymerization using a peroxide-based, redox, or azo-based initiator that can be used in emulsion polymerization, and the redox initiator may be at least one selected from the group consisting of t-butyl hydroperoxide, diisopropylbenzene hydroperoxide, and cumene hydroperoxide, for example, and in this case, there is an effect of providing a stable polymerization environment. When the redox initiator is used, it may be further performed by including ferrous sulfide, sodium ethylenediaminetetraacetate, and sodium formaldehyde sulfoxylate as a redox catalyst that is an activator, and the weight average molecular weight of the shell may be adjusted to 40,000 g / mol or less by adjusting the input amount of the redox initiator and the redox catalyst.
[0062] According to an embodiment of the present invention, the step (S2) may be performed by continuously adding the graft monomer. If the graft monomer is added all at once before the start of the graft polymerization reaction in the step (S2), a problem of an increase in the weight average molecular weight of the shell may occur.
[0063] According to one embodiment of the present invention, the emulsion polymerization in the step (S1) and the step (S2) may be carried out in an aqueous solvent, and the aqueous solvent may be ion-exchanged water.
[0064] According to one embodiment of the present invention, the method for preparing the graft copolymer may include a step (S3) of coagulating and drying the graft copolymer latex prepared in the step (S2) to obtain a powder form.
[0065] The present invention also provides a curable resin composition. The curable resin composition may contain the graft copolymer as an impact modifier, and as a specific example, the graft copolymer may be dispersed in a powder form.
[0066] According to one embodiment of the present invention, the curable resin composition may include a continuous phase and a dispersed phase, the continuous phase may include a curable resin, and the dispersed phase may include the graft copolymer. As a specific example, the curable resin composition may include 50% to 99% by weight, 50% to 80% by weight, or 50% to 70% by weight of the continuous phase; and 1% to 50% by weight, 20% to 50% by weight, or 30% to 50% by weight of the dispersed phase.
[0067] According to one embodiment of the present invention, the curable resin may be a thermosetting resin or a photocurable resin, and a specific example thereof may be one or more selected from the group consisting of an epoxy resin, a phenolic resin, an unsaturated polyester resin, a melamine resin, and a urea resin, and a more specific example thereof may be an epoxy resin.
[0068] According to an embodiment of the present invention, the epoxy resin may include at least two epoxy bonds, and specific examples thereof may be one or more selected from the group consisting of bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, bisphenol E type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, and glycidylamine type epoxy resins.
[0069] According to an embodiment of the present invention, the curable resin composition may further include a curing agent in addition to the curable resin and the graft copolymer, and the curing agent may be at least one selected from the group consisting of an acid anhydride curing agent, an amine-based curing agent, and a phenol-based curing agent.
[0070] According to one embodiment of the present invention, the acid anhydride curing agent may be at least one selected from the group consisting of phthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylhimic anhydride, methylcyclohexene dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, dodecenyl succinic anhydride, polyazelaic anhydride, and poly(ethyloctadecanedioic) anhydride.
[0071] According to an embodiment of the present invention, the amine-based curing agent may be 2,5(2,6)-bis(aminomethyl)bicyclo[2,2,1]heptane, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, diethyltoluenediamine, 3,3'-diaminodiphenylsulfone (3,3'-DDS), 4,4'-diaminodiphenylsulfone (4,4'-DDS), diaminodiphenylether (DADPE), bisaniline, bis(aminomethyl)cyclohexane ... phosphorus, benzyldimethylaniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4,4'-diaminodiphenylmethane, 2,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,4-diaminophenol, 2,5-diaminophenol, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 2,3-tolylenediamine, 2,4-tolylenediamine, 2,5-tolylenediamine, 2,6-tolylenediamine, 3,4-tolylenediamine, methylthiotoluenediamine, diethyltoluenediamine, and dicyandiamide.
[0072] According to one embodiment of the present invention, the phenol-based curing agent may be at least one selected from the group consisting of phenol novolac resin, cresol novolac resin, bisphenol A, bisphenol F, bisphenol AD, and diallyl derivatives of bisphenols.
[0073] According to an embodiment of the present invention, the curable resin composition may further include additives in addition to the curable resin and the graft copolymer. The additives may be release agents such as silicone oil, natural wax, and synthetic wax; powders such as crystalline silica, fused silica, calcium silicate, and alumina; fibers such as glass fiber and carbon fiber; flame retardants such as antimony trioxide; halogen trapping agents such as hydrotalcite and rare earth oxides; colorants such as carbon black and red iron oxide; and silane coupling agents.
[0074] The present invention also provides a method for producing the curable resin composition. According to one embodiment of the present invention, the method for preparing the curable resin composition includes a step (S10) of preparing a graft copolymer latex containing the graft copolymer, a step (S20) of preparing a graft copolymer powder by agglomerating and drying the graft copolymer latex prepared in the step (S10), and a step (S30) of preparing a curable resin composition by mixing a curable resin and the graft copolymer powder prepared in the step (S20), and the step (S30) may be performed by dispersing using a stirrer.
[0075] According to an embodiment of the present invention, the step (S10) may be performed by the above-mentioned method for preparing the graft copolymer in the step for preparing the graft copolymer.
[0076] According to one embodiment of the present invention, the step (S20) is a step for obtaining the graft copolymer prepared in the step (S10) in a powder form, and may be performed by coagulating and drying the graft copolymer latex prepared in the step (S10).
[0077] According to one embodiment of the present invention, the aggregation in step (S20) may be performed by adding a coagulant to the graft copolymer latex. The aggregation in step (S20) may be performed by acid coagulation, such as with an aqueous sulfuric acid solution, and salt coagulation, such as with sodium chloride or sodium sulfate, and both acid coagulation and salt coagulation may be performed as necessary. In this case, the acid coagulation and salt coagulation may be performed simultaneously or stepwise. When the aggregation is performed stepwise, acid coagulation may be performed first and then salt coagulation, or salt coagulation may be performed first and then acid coagulation. The aggregation in step (S20) may be performed in the presence of an organic dispersant as necessary.
[0078] According to one embodiment of the present invention, the drying in step (S20) may be carried out by a conventional drying method, and may further include a step of dehydrating the coagulated graft copolymer latex prior to drying, if necessary.
[0079] According to one embodiment of the present invention, the step (S30) is a step of mixing the curable resin and the graft copolymer by the above-mentioned powder dispersion method when the graft copolymer is applied to the curable resin as an impact modifier, and may be performed by adding the graft copolymer powder to the curable resin and mixing it. As described above, the graft copolymer according to the present invention has excellent powder dispersibility, so it can be directly dispersed in the curable resin in powder form. As a specific example, the viscosity of the curable resin composition prepared in the step (S30) may be 2,500 Pa.s or less, 2,000 Pa.s or less, 100 Pa.s to 2,000 Pa.s, 500 Pa.s to 1,800 Pa.s, or 1,000 Pa.s to 1,600 Pa.s at 25°C, and within this range, the viscosity of the graft copolymer powder is low, so the dispersibility is excellent.
[0080] The present invention also provides an adhesive composition comprising the curable resin composition. The adhesive composition may contain the curable resin composition as a reinforcement agent. According to an embodiment of the present invention, the adhesive composition may contain, in addition to the reinforcing agent, a base agent, a urethane resin, a curing agent, a curing accelerator, a filler, and the like that can be used in an adhesive.
[0081] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a schematic diagram of a semiconductor device according to an embodiment of the present invention;
[0082] Working Example Example 1 <Production of Rubber Polymer Latex> In a polymerization reactor (autoclave) substituted with nitrogen, 75 parts by weight of ion-exchanged water, 60 parts by weight of 1,3-butadiene, 1.4 parts by weight of potassium resin acid salt, 0.6 parts by weight of potassium oleate, and potassium carbonate (K 2 CO 3 ) 0.9 parts by weight, t-dodecyl mercaptan 0.3 parts by weight, potassium persulfate (K 2 S 2 O 8 0.3 parts by weight of 1,3-butadiene was added in one lump, and polymerization was carried out at a reaction temperature of 70°C. Next, when the polymerization conversion rate was 30% to 40%, 0.7 parts by weight of potassium oleate was added in one lump, and then 20 parts by weight of 1,3-butadiene was added in one lump, and polymerization was continued at a reaction temperature of 70°C. Next, after the polymerization conversion rate reached 60%, 20 parts by weight of 1,3-butadiene was added in one lump, and the reaction temperature was raised to 80°C, and polymerization was continued, and the reaction was terminated when the polymerization conversion rate reached 95%. The total time required for polymerization was 23 hours, the gel content of the obtained rubber polymer latex was 76%, and the average particle size of the rubber polymer particles was 300 nm. In this case, the polymerization conversion rate was calculated as the ratio of the solid weight of the obtained rubber polymer to the solid weight of the input monomers.
[0083] <Production of graft copolymer latex> In a nitrogen-substituted sealed polymerization reactor, 80 parts by weight of the rubber polymer latex produced above was added based on 100 parts by weight of the total content of the rubber polymer latex (based on solid content), methyl methacrylate, and n-butyl acrylate, and 200 parts by weight of ion-exchanged water, 0.2 parts by weight of potassium oleate, 0.036 parts by weight of ferrous sulfide, 0.2 parts by weight of sodium ethylenediaminetetraacetate, 0.2 parts by weight of sodium formaldehyde sulfoxylate, and 0.4 parts by weight of t-butyl hydroperoxide were added all at once. Then, 16 parts by weight of methyl methacrylate, 3 parts by weight of n-butyl acrylate, and 1 part by weight of styrene were continuously added for 3 hours, and polymerization was carried out at a reaction temperature of 60°C for 4 hours to produce a graft copolymer latex. The final polymerization conversion was 98.3%, and the average particle size of the graft copolymer particles was 318 nm. The polymerization conversion rate was calculated as the ratio of the solid weight of the obtained graft copolymer to the solid weight of the rubber polymer and monomers charged.
[0084] <Production of Graft Copolymer Powder> The graft copolymer latex prepared above was diluted with distilled water to 15% by weight based on solid content, and then placed in a coagulation tank, and the internal temperature of the coagulation tank was increased to 45° C. Thereafter, IR1076 was added as an antioxidant based on 100 parts by weight based on the solid content of the graft copolymer, and the mixture was coagulated by stirring while adding an aqueous sulfuric acid solution, and the graft copolymer and water were separated, followed by dehydration and drying to produce a graft copolymer powder.
[0085] Example 2 The rubber polymer latex was prepared in the same manner as in Example 1, except that 1.7 parts by weight of potassium resin salt was added instead of 1.4 parts by weight, and 0.7 parts by weight of potassium oleate was added instead of 0.6 parts by weight. The average particle size of the rubber polymer particles was 255 nm, and the average particle size of the graft copolymer particles was 264 nm.
[0086] Example 3 The rubber polymer latex was prepared in the same manner as in Example 1, except that 1.0 part by weight of potassium resin acid was added instead of 1.4 parts by weight, and 0.4 part by weight of potassium oleate was added instead of 0.6 parts by weight. The average particle size of the rubber polymer particles was 338 nm, and the average particle size of the graft copolymer particles was 374 nm.
[0087] Example 4 The same procedure as in Example 1 was repeated, except that 0.072 parts by weight of ferrous sulfide instead of 0.036 parts by weight, 0.4 parts by weight of sodium ethylenediaminetetraacetate instead of 0.2 parts by weight, 0.4 parts by weight of sodium formaldehyde sulfoxylate instead of 0.2 parts by weight, and 0.8 parts by weight of t-butyl hydroperoxide instead of 0.4 parts by weight were added when preparing the graft copolymer latex. The average particle size of the prepared graft copolymer particles was 320 nm.
[0088] Example 5 The same procedure as in Example 1 was repeated, except that 0.024 parts by weight of ferrous sulfide instead of 0.036 parts by weight, 0.14 parts by weight of sodium ethylenediaminetetraacetate instead of 0.2 parts by weight, 0.14 parts by weight of sodium formaldehyde sulfoxylate instead of 0.2 parts by weight, and 0.27 parts by weight of t-butyl hydroperoxide instead of 0.4 parts by weight were added when preparing the graft copolymer latex. The average particle size of the prepared graft copolymer particles was 325 nm.
[0089] Comparative Example 1 The same procedure as in Example 1 was repeated, except that the rubber polymer latex was added in an amount of 85 parts by weight instead of 80 parts by weight based on the solid content, 12 parts by weight instead of 16 parts by weight of methyl methacrylate, 2.5 parts by weight instead of 3 parts by weight of n-butyl acrylate, and 0.5 parts by weight instead of 1 part by weight of styrene, when preparing the graft copolymer latex. The average particle size of the prepared graft copolymer particles was 305 nm.
[0090] Comparative Example 2 The same procedure as in Example 1 was repeated, except that the rubber polymer latex was added in an amount of 70 parts by weight instead of 80 parts by weight based on the solid content, methyl methacrylate was added in an amount of 24 parts by weight instead of 16 parts by weight, n-butyl acrylate was added in an amount of 4 parts by weight instead of 3 parts by weight, and styrene was added in an amount of 2 parts by weight instead of 1 part by weight. The average particle size of the graft copolymer particles prepared in this example was 330 nm.
[0091] Comparative Example 3 The same procedure as in Example 1 was repeated, except that 0.018 parts by weight of ferrous sulfide instead of 0.036 parts by weight, 0.1 parts by weight of sodium ethylenediaminetetraacetate instead of 0.2 parts by weight, 0.1 parts by weight of sodium formaldehyde sulfoxylate instead of 0.2 parts by weight, and 0.2 parts by weight of t-butyl hydroperoxide instead of 0.4 parts by weight were added during the preparation of the graft copolymer latex. The average particle size of the prepared graft copolymer particles was 321 nm.
[0092] Comparative Example 4 The same procedure as in Example 1 was carried out, except that the graft copolymer latex was prepared as follows.
[0093] <Production of graft copolymer latex> In a nitrogen-substituted sealed polymerization reactor, 80 parts by weight of the rubber polymer latex produced above was added based on 100 parts by weight of the total content of the rubber polymer latex (based on solid content), methyl methacrylate, and n-butyl acrylate, and 200 parts by weight of ion-exchanged water, 0.2 parts by weight of potassium oleate, 16 parts by weight of methyl methacrylate, 3 parts by weight of n-butyl acrylate, and 1 part by weight of styrene were added all at once. Then, 0.036 parts by weight of ferrous sulfide, 0.2 parts by weight of sodium ethylenediaminetetraacetate, 0.2 parts by weight of sodium formaldehyde sulfoxylate, and 0.4 parts by weight of t-butyl hydroperoxide were added all at once. Then, polymerization was carried out at a reaction temperature of 60°C for 4 hours to produce a graft copolymer latex. The final polymerization conversion was 98.9%, and the average particle size of the graft copolymer particles was 318 nm. The polymerization conversion rate was calculated as the ratio of the solid weight of the obtained graft copolymer to the solid weight of the rubber polymer and monomers charged.
[0094] Comparative Example 5 The rubber polymer latex was prepared in the same manner as in Example 1, except that 2.0 parts by weight of potassium resin acid salt was added instead of 1.4 parts by weight, and 0.8 parts by weight of potassium oleate salt was added instead of 0.6 parts by weight. The average particle size of the rubber polymer particles was 200 nm, and the average particle size of the graft copolymer particles was 211 nm.
[0095] Experimental Example 1 For the rubber polymers and graft copolymers prepared in Examples 1 to 5 and Comparative Examples 1 to 5, the average particle diameters of the core and graft copolymers and the weight average molecular weights of the shell were measured by the following methods, and the contents of each component and the method of adding the graft monomer during the preparation of the graft copolymers are shown in Tables 1 and 2 below.
[0096] Average particle size (nm) of core and graft copolymer: The rubber polymer latex and graft copolymer latex prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were each diluted with distilled water to a concentration of 200 ppm, and then measured by dynamic light scattering (DLS) method according to ISO 22412 using NICOMP 380.
[0097] Weight average molecular weight of shell (g / mol): The weight average molecular weight of the shell in the core-shell graft copolymer obtained above was measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.
[0098] In this case, the sample was prepared by taking a portion of the graft copolymer solution dispersed in tetrahydrofuran, separating the precipitate using a centrifug, and then filtering the upper layer through a 0.45μm PTFE syringe filter to use as the sample solution. The graft copolymer was sampled at a standard concentration of 30.0mg / mL, and the linear polymer at 1.5mg / mL.
[0099] -Column: PL MiniMixed B x 2 -Solvent: Tetrahydrofuran (Stabilized with BHT) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 100μl -Column temperature: 30℃ -Detector: Waters 2414 Refractive Index Detector -Data processing: Empower 3
[0100] [Table 1]
[0101] [Table 2]
[0102] As shown in Tables 1 and 2, it was confirmed that the graft copolymers of Examples 1 to 5 prepared according to the present invention had the core content, average particle diameter of the core, and weight average molecular weight of the shell within the ranges defined in the present invention.
[0103] On the other hand, it was confirmed that in Comparative Example 1, the content of the core in the graft copolymer was excessive, in Comparative Example 2, the content of the core in the graft copolymer was small, in Comparative Example 3, the weight average molecular weight of the shell was high, in Comparative Example 4, the weight average molecular weight of the shell was very high due to the lump-sum addition of the graft monomers, and in Comparative Example 5, the average particle size of the core was small.
[0104] Experimental Example 2 Using the graft copolymer powders produced in the above Examples 1 to 5 and Comparative Examples 1 to 5, epoxy resin compositions in which the graft copolymers were dispersed in a curable resin composition were produced by the following method.
[0105] <Production of Epoxy Resin Composition Having Graft Copolymer Dispersed> 60 parts by weight of epoxy resin (KUKDO CHEMICAL, YD-128) and 40 parts by weight of the graft copolymer powder prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were added to a planetary mixer (KMTECH, KPLM-0.6) set at 70°C, based on a total content of 100 parts by weight of epoxy resin and graft copolymer, and the mixture was stirred at 10 rpm for 1 hour, 80 rpm for 2 hours, and 60 rpm for 10 hours to disperse the graft copolymer powder in the epoxy resin, thereby preparing an epoxy resin composition in which the graft copolymer is dispersed.
[0106] The dispersion state of the graft copolymer in the epoxy resin composition prepared above was confirmed by the following method, and the viscosity was measured. The results are shown in Tables 3 and 4 below. Dispersion state: An epoxy resin composition was applied to a cold-rolled (CR) steel plate measuring 25 mm x 100 mm to a thickness of 0.2 mm, and the number of particles observed with the naked eye was counted. In this case, if the number of particles observed with the naked eye is less than 10, it indicates an excellent dispersion state, if it is 10 to less than 50, it indicates an average dispersion state, and if it is 50 or more, it indicates a poor dispersion state.
[0107] Viscosity at 25°C (Pa.s): The viscosity of the epoxy resin composition prepared above was measured at 25°C using a rheometer (Anton Paar, MRC 302) at a shear rate of 2.4 s -1 The viscosity values at 100 s are shown.
[0108] [Table 3]
[0109] [Table 4]
[0110] As shown in Tables 3 and 4, it was confirmed that the curable resin composition in which the graft copolymer of the present invention is applied in powder form as an impact modifier has excellent dispersibility, not to mention a sufficient dispersion state of the graft copolymer powder, since the viscosity at 25°C is low.
[0111] In contrast, in Comparative Example 1, the content of the core in the graft copolymer was excessive, so that the compatibility between the curable resin and the graft copolymer was rapidly reduced, and although the increase in viscosity due to the swelling of the shell could be prevented, it was confirmed that dispersion was not substantially performed.
[0112] In addition, in Comparative Example 2, since the core content in the graft copolymer was low, the shell content in the graft copolymer increased, and it was confirmed that the shell, which has high affinity with the epoxy resin, swelled, increasing the viscosity and decreasing the dispersibility.
[0113] Moreover, in Comparative Example 3, it was confirmed that since the weight average molecular weight of the shell was high, the shell, which has high affinity with the epoxy resin, swelled, increasing the viscosity and decreasing the dispersibility.
[0114] In addition, in Comparative Example 4, the weight average molecular weight of the shell was very high because the graft monomer was added all at once during the graft polymerization. As a result, it was confirmed that the shell, which has high affinity with the epoxy resin, swelled, increasing the viscosity and decreasing the dispersibility.
[0115] In addition, in the case of Comparative Example 5, in which the average particle size of the core was small, the average particle size of the core and the resulting average particle size of the graft copolymer were not large enough, so aggregation occurred between small particles, and it was confirmed that dispersibility decreased due to an increase in viscosity.
[0116] Experimental Example 3 Using the epoxy resin composition prepared in Experimental Example 2, a structural adhesive composition was prepared in the following manner.
[0117] <Structural adhesive composition> An epoxy resin (KUKDO CHEMICAL, YD-128) as a base material, an epoxy resin composition (weight ratio of epoxy resin:graft copolymer powder=60:40) according to each of Examples 1 to 5 and Comparative Examples 1 to 5 prepared in Experimental Example 2 as a reinforcing agent, a urethane resin (Adeka, QR-9466), a curing agent (Evonik, Dicyanex 1400F), a curing accelerator (Evonik, Amicure UR7 / 10), calcium oxide (Youyeong Materials, UNI-OX), and fumed silica (Cabot, CAB-O-SIL TS-720) were mixed in the amounts shown in Tables 5 and 6 below using a paste mixer (KMTECH, PDM-300) at 600 rpm revolution and 500 rpm rotation for 3 minutes, and then degassed at 600 rpm revolution and 200 rpm rotation for 5 minutes to prepare an adhesive composition. At this time, the curing agent was added in an amount according to the equivalent weight of the epoxy resin, and the curing accelerator was added in an equivalent ratio of 1 / 7 of the curing agent.
[0118] The impact peel strength of the structural adhesive composition prepared above was measured by the following method, and the results are shown in Tables 5 and 6 below. Impact peel strength (N / mm): The impact peel strength of the structural adhesive composition prepared above was measured according to the standard ISO 11343. The size of the test piece was 90 mm x 20 mm x 1.6T (mm), and the size of one side to which the adhesive composition was applied was 30 mm x 20 mm. After removing contaminants from one side of the test piece using ethanol, the structural adhesive composition prepared above was applied. The thickness of the adhesive composition was kept constant using microbeads, and another test piece was covered and fixed on top of it, and then cured at 180 ° C for 30 minutes. After curing, the specimen was stabilized at 25 ° C and -40 ° C for more than 1 hour, and then a load was applied at a speed of 2 m / sec using an impact strength tester (INSTRON, 9350), and the impact peel strength according to the shear strength was measured.
[0119] [Table 5]
[0120] [Table 6]
[0121] As shown in Tables 5 and 6, the curable resin composition of the present invention has excellent dispersibility because the graft copolymer powder is sufficiently dispersed and has low viscosity at 25° C. As a result, it was confirmed that when applied as a reinforcing agent to an adhesive composition, the impact peel strength of the structural adhesive composition is excellent at both room temperature (25° C.) and low temperature (-40° C.).
[0122] In contrast, when the curable resin compositions of Comparative Examples 1 to 5 were used as reinforcing agents, it was confirmed that the impact peel strength at room temperature and / or low temperature decreased, which was due to a decrease in the dispersibility of the powdered graft copolymer in the curable resin.
[0123] From these results, it was confirmed that the graft copolymer of the present invention has excellent powder dispersibility in curable resins such as epoxy resins, and therefore can be dispersed in a curable resin composition by a powder dispersion method, thereby providing excellent productivity for the curable resin composition, and that the graft copolymer dispersed in the curable resin composition can improve mechanical properties such as impact resistance.
Claims
1. A core-shell graft copolymer comprising a core containing a rubber polymer and a shell formed by graft polymerizing a graft monomer onto the rubber polymer, The graft copolymer comprises 72% to 83% by weight of the core; The core has an average particle size of 250 nm or more, A part of the graft copolymer solution dispersed in tetrahydrofuran is taken, and the precipitate is separated using a centrifuge. The supernatant is taken and filtered through a 0.45 μm PTFE syringe filter. The weight average molecular weight of the sample is 40,000 g / mol or less. The graft monomer includes a methyl (meth)acrylate monomer and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms; Graft copolymer.
2. 2. The graft copolymer according to claim 1, wherein the rubber polymer comprises at least one monomer unit selected from the group consisting of conjugated diene monomer units and alkyl acrylate monomer units.
3. The graft copolymer according to claim 1 or 2, wherein the rubber polymer is at least one selected from the group consisting of a homopolymer of a conjugated diene monomer, a copolymer of an aromatic vinyl monomer and a conjugated diene monomer, and an acrylic rubber polymer.
4. The graft copolymer according to any one of claims 1 to 3, wherein the graft monomer comprises at least one selected from the group consisting of alkyl (meth)acrylate monomers and aromatic vinyl monomers.
5. The graft copolymer according to any one of claims 1 to 4, wherein the graft monomer comprises an aromatic vinyl monomer and a crosslinkable monomer.
6. The graft copolymer of claim 5 , wherein the cross-linking monomer is polyethylene glycol diacrylate or allyl methacrylate.
7. The graft copolymer of any one of claims 1 to 6, wherein the graft copolymer comprises 75% to 80% by weight of the core and 20% to 25% by weight of the shell.
8. The graft copolymer according to any one of claims 1 to 7, wherein the core has an average particle size of 250 nm to 350 nm.
9. The graft copolymer according to any one of claims 1 to 8, wherein a part of the graft copolymer solution dispersed in tetrahydrofuran is taken, a precipitate is separated using a centrifuge, and the supernatant is taken and filtered through a 0.45 μm PTFE syringe filter to obtain a sample having a weight average molecular weight of 30,000 g / mol to 40,000 g / mol.
10. The graft copolymer according to any one of claims 1 to 9, wherein the graft copolymer has an average particle size of 250 nm to 500 nm.
11. Contains a continuous phase and a dispersed phase, the continuous phase comprises a curable resin; A curable resin composition, wherein the dispersed phase comprises the graft copolymer according to any one of claims 1 to 10.
12. 12. The curable resin composition of claim 11, wherein the curable resin composition comprises 50% to 99% by weight of the continuous phase and 1% to 50% by weight of the dispersed phase.
13. The curable resin composition according to claim 11 or 12, wherein the curable resin is an epoxy resin.
14. A step (S10) of producing a graft copolymer latex containing the graft copolymer according to any one of claims 1 to 10; (S20) agglomerating and drying the graft copolymer latex prepared in the (S10) step to prepare a graft copolymer powder; (S30) mixing the curable resin and the graft copolymer powder prepared in the (S20) step to prepare a curable resin composition; Including, The method for producing a curable resin composition, wherein the step (S30) is carried out by dispersing using a stirrer.
15. The method for producing a curable resin composition according to claim 14, wherein the viscosity of the curable resin composition produced in the step (S30) is 2,500 Pa.s or less at 25°C.
Citation Information
Patent Citations
JP1975128744A
Graft copolymer resin composition using the same or its plated product
JP2000034321A
Thermosetting resin composition and its use
JP2006104328A
Thermoplastic resin composition for direct vapor deposition, molded product and lamp
JP2007284469A
Surface conductive laminated sheet and electronic part packaging container
WO2011118522A1